2020
DOI: 10.1016/j.bpj.2019.11.304
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Structural Pleiotropy and Regulatory Evolution in the Retention of Heteromers of Paralogs

Abstract: the conserved transmembrane domains, created a structure-based multiple sequence alignment, and analyzed global protein fold similarity, pore size, and ligand binding pockets. Leveraging the wealth of structural information provides insight into commonalities and differences among TRP channels and generates testable hypotheses for future functional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…coli protein-protein interaction (PPI) data, [ 3 ] reported that most oligomeric paralogs diverged to form obligatory homomers. However, analysis of yeast, worm and fly, using both PPI data and oligomers of known structure, [ 2 ] indicated that heteromeric interactions dominate, a conclusion recently supported by [ 4 ] who analyzed yeast PPI data. We compared these studies and observed that these inconsistencies relate to three major factors.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…coli protein-protein interaction (PPI) data, [ 3 ] reported that most oligomeric paralogs diverged to form obligatory homomers. However, analysis of yeast, worm and fly, using both PPI data and oligomers of known structure, [ 2 ] indicated that heteromeric interactions dominate, a conclusion recently supported by [ 4 ] who analyzed yeast PPI data. We compared these studies and observed that these inconsistencies relate to three major factors.…”
Section: Introductionmentioning
confidence: 92%
“…Does protein function, or the source organism, for example, affect which fate dominates? Genome-scale studies [ 2 4 ] attempted to address the relative frequencies of these scenarios in model organisms, but their conclusions are inconsistent. Analyzing human, Arabidopsis , yeast and E .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the ant species, they secrete similar molecules, which allow for the recognition of their ally and keep them from attacking each other (Menzel et al, 2013;Menzel, Linsenmair, & Blüthgen, 2008). Finally, a higher overall protein sequence similarity between paralogs favors the retention of their interactions with the same partners, including with one another (Ispolatov, Yuryev, Mazo, & Maslov, 2005;Lukatsky, Shakhnovich, Mintseris, & Shakhnovich, 2007;Lukatsky, Zeldovich, & Shakhnovich, 2006;Marchant et al, 2019).…”
Section: E Voluti On Of Noveltie S In B Iolog Ic Al Sys Temsmentioning
confidence: 99%